The Effects of Moderate and Low-Intensity Resistance Exercise on HbA1c Reduction in Patients with Type 2 Diabetes Mellitus - Diah Ratri Larasati; Haryanto Haryanto; Lidia Hastuti; Suriadi Jais; Imran Imran (Jurnal Kesehatan Manarang, 2026)
Type 2 diabetes mellitus (T2DM) is a long-term metabolic disorder whose prevalence continues to rise worldwide. This study aims to examine the effectiveness of moderate-intensity resistance exercise compared with low-intensity resistance exercise and no exercise on glycemic control among patients with type 2 diabetes mellitus (T2DM). Methods: A quasi-experimental pre–posttest design with three parallel groups was used: a control group receiving standard care without exercise, a low-intensity resistance exercise group, and a moderate-intensity resistance exercise group (total N = 51 participants). The intervention consisted of a 12-week resistance exercise program (three sessions per week) using elastic loop bands with different resistance levels. Outcomes included anthropometric measures, blood pressure, glycemic parameters (HbA1c, fasting, and random blood glucose), and self-care behaviors assessed with the Summary of Diabetes Self-Care Activities (SDSCA) questionnaire. Eligible participants were adults aged 25–75 years with T2DM who were receiving oral and/or injectable therapy, without exercise contraindications, and able to provide consent. Individuals with severe diabetic complications, participation in other exercise programs, or medical conditions affecting HbA1c were excluded. Data were analyzed using paired t-tests and one-way ANOVA with Tukey post hoc tests. Results: The moderate-intensity group experienced a statistically significant reduction in mean HbA1c of 0.85% (p = 0.016). Changes in the control group (−0.23%) and low-intensity group (0.06%) were not statistically significant. Tukey post hoc analysis confirmed that HbA1c reduction in the moderate-intensity group was significantly greater than in the control group (mean difference, −1.03%; p = 0.004). However, the difference between moderate- and low-intensity groups was not significant (mean difference, −0.34%; p = 0.516). Conclusion: Moderate-intensity resistance exercise significantly improves glycemic control in patients with type 2 diabetes mellitus (T2DM). Adding structured moderate-intensity resistance training to non-pharmacological diabetes management can improve glycemic outcomes.